What RNAi screens in model organisms revealed about microbicidal response in mammals? - Abnave, Prasad; Conti, Filippo; Torre, Cedric; Ghigo, Eric (Frontiers in Cellular and Infection Microbiology, 2015)
The strategies evolved by pathogens to infect hosts and the mechanisms used by the host to eliminate intruders are highly complex. Because several biological pathways and processes are conserved across model organisms, these organisms have been used for many years to elucidate and understand the mechanisms of the host-pathogen relationship and particularly to unravel the molecular processes enacted by the host to kill pathogens. The emergence of RNA interference (RNAi) and the ability to apply it toward studies in model organisms have allowed a breakthrough in the elucidation of host-pathogen interactions. The aim of this mini-review is to highlight and describe recent breakthroughs in the field of host-pathogen interactions using RNAi screens of model organisms. We will focus specifically on the model organisms Drosophila melanogaster, Caenorhabditis elegans and Danio rerio. Moreover, a recent study examining the immune system of Planarian will be discussed.